Defining the altered glycoproteomic space of the early secretory pathway by class I mannosidase pharmacological inhibition - Munteanu, Cristian V. A.; Chirițoiu, Gabriela N.; Petrescu, Andrei-Jose; Petrescu, Ștefana M. (Frontiers in Molecular Biosciences, 2023)
N-glycosylation is a key process for various biological functions like protein folding, maturation and sorting for the conventional secretory compartment, cell-cell communication and immune response. This is usually accomplished by a complex system of mannosidases in which those from class I have an outstanding role. These are usually involved in the early protein sorting associated to the Endoplasmic Reticulum (ER) in the N-glycan dependent quality control (ERQC) and ER-associated degradation (ERAD). Although these are vital processes in maintaining cellular homeostasis, studies regarding large-scale analysis of this pool of molecules, further denoted as proteins from the early secretory pathway (ESP), were limited addressed. Here, using a custom workflow employing a combination of glycomics and deglycoproteomics analyses, using lectin affinity and selective Endoglycosidase H (Endo H) digestion towards oligomannose and hybrid carbohydrate structures, we scrutinize the steady-state oligomannosidic glycoprotein load and further delineate the ESP fraction in melanoma cells. All of these were assessed by applying our workflow for glycosite relative quantification of both the peptide chain and carbohydrate structure in cells with suppressed activity of class I mannosidases using kifunensine. We found that most of the ESP are transient clients involved in cell-extracellular matrix communication, particularly integrin-mediated communication which adopt Man9 N-glycans in kifunensine-treated cells. Moreover, our results reveal that core-fucosylation is decreased following inhibition of class I mannosidases and this could be explained by a general lower protein level of FUT8, the enzyme responsible for fucosylation. By comparing our data with results obtained following downregulation of a key mannosidase in misfolded protein degradation, we mapped both novel and previously suggested endogenous substrate candidates like PCDH2, HLA-B, LAMB2 or members of the integrin family of proteins such as ITGA1 and ITGA4, thus validating the findings obtained using our workflow regarding accumulation and characterization of ESP transitory members following mannosidase class I inhibition. This workflow and the associated dataset not only allowed us to investigate the oligomannosidic glycoprotein fraction but also to delineate differences mediated at glycosite-level upon kifunensine treatment and outline the potential associated cellular responses.